MUTATION BREEDING IN POTATO; ENDEAVORS AND CHALLENGES - M. A. B. Zia; A. Bakhsh; M. E. Çalıskan (Journal of Animal and Plant Sciences, 2018)
Mutation breeding is a resolute application of mutations to develop the desired characteristics in crops to get increased yield. Since the first release of mutant potato cultivar in Belgium in 1968, mutation breeding in potato found a niche in plant breeding because of the increased quality and yield improvements. Six mutated potato cultivars have been registered from all over the world. Many scientists are working on potato mutation breeding and have reported appreciable results especially quality improvement of the crop, decreased amylose contents, salt and heat tolerance, and resistance to late blight. However conventionally induced mutation has some distinct limitations, especially in the applications of crop-breeding, as percentage of desired mutation is very less in the field; by using in vitro techniques with the combination of routine mutagenesis has overawed this obstruction too. Thus this technique can be the part of the other plant breeding techniques to increase the yield and to nourish the rapidly increasing world’s population. The present review focuses the achievements, endeavors and future challenges of mutation breeding in potato.
Keywords: conventional approaches; in vitro; biotic and abiotic; quality